New Insights on Cosmic Ray Modulation through a Joint Use of Nonstationary Data-Processing Methods. (9th December 2012) - Vecchio, A.; Laurenza, M.; Storini, M.; Carbone, V.
Abstract : The time variability of the cosmic ray (CR) intensity, recorded by the Climax neutron monitor and covering the period 1953–2004, has been analyzed by the joint application of the wavelet and the empirical mode decomposition (EMD) analyses. Dominant time scales of variability are found at 11 yr, 22 yr, 6 yr and in the range of the quasi-biennial oscillations (QBOs). The combination of the 11 yr cycle and QBOs explains the Gnevychev Gap (GG) phenomenon and many step-like decreases characterizing the CR modulation. The additional scales of variability at 22 yr and 6 yr are responsible for other features of the long-term CR trend, such as the intensity flat-topped profile, following the maxima of even-numbered cycles during positive polarity state of the heliosphere (A > 0 ). Comparison with basic time scales of variability derived from the sunspot area (SA) allows the association of the 11 yr cycle and QBOs with solar activity variations, whereas the other two modes with the drift effects govern the CR entrance in the heliosphere.